Management of Critical Limb Ischemia. (February 2016) - Kinlay, Scott
Abstract : Critical limb ischemia (CLI) is a clinical syndrome of ischemic pain at rest or tissue loss, such as nonhealing ulcers or gangrene, related to peripheral artery disease. CLI has a high short-term risk of limb loss and cardiovascular events. Noninvasive or invasive angiography help determine the feasibility and approach to arterial revascularization. An endovascular-first approach is often advocated based on a lower procedural risk; however, specific patterns of disease may be best treated by open surgical revascularization. Balloon angioplasty and stenting form the backbone of endovascular techniques, with drug-eluting stents and drug-coated balloons offering low rates of repeat revascularization. Combined antegrade and retrograde approaches can increase success in long total occlusions. Below the knee, angiosome-directed angioplasty may lead to greater wound healing, but failing this, any straight-line flow into the foot is pursued. Hybrid surgical techniques such as iliac stenting and common femoral endarterectomy are commonly used to reduce operative risk. Lower extremity bypass grafting is most successful with a good quality, long, single-segment autogenous vein of at least 3.5-mm diameter. Minor amputations are often required for tissue loss as a part of the treatment strategy. Major amputations (at or above the ankle) limit functional independence, and their prevention is a key goal of CLI therapy. Medical therapy after revascularization targets risk factors for atherosclerosis and assesses wound healing and new or recurrent flow-limiting disease. The ongoing National Institutes of Health–sponsored Best Endovascular Versus Best Surgical Therapy in Patients With Critical Limb Ischemia (BEST-CLI) study is a randomized trial of the contemporary endovascular versus open surgical techniques in patients with CLI.